Fretting wear studies of aeroengine materials - Soh, Hian Ping (2006)
As long as there is a certain degree of flexibility i.e. relative motion, the contacting surface of a mechanical component will experience fretting damage, in the form of fretting wear and/or fretting fatigue, depending on the loading conditions and performance requirements. In the present investigations, the fretting wear behaviour of aeroengine materials were studied by both experimental (mainly gross slip regime) and finite element approaches involving the various aspects of fretting variables (applied normal load, strokes, wear duration, material hardness, lubrication and etc. ) that affects the material tribosystem. The aeroengine materials are the Super S/CMV and AerMet®l00 ultrahigh strength steel alloys and Inconel 718 nickel-base superalloys. The present works highlights a number of issues important to fretting damage, which involves studying: (1) the effect of nitriding and lubrication on Super S/CMV steel experimentally and wear data validation and prediction by FEM based on a modified Archard's equation; (2) the effect of moderate temperature on the fretting behaviour of Inconel 718 alloy; (3) the different material combinations (Super S/CMV, AerMet®100, and Inconel 718) on fretting wear. The following experimental tools are utilised to investigate the morphological changes of the contacting surfaces during fretting. A simple crossed round-on-flat arrangement was used to determine the coefficients of friction and the wear coefficients applicable to the contact configuration and loading conditions. Surface topography changes were investigated by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The presence of various phases and elements were analysed by x-ray diffraction (XRD) and energy dispersive x-ray (EDX). The wear depth and wear width were profiled using a surface profilometer for the wear coefficient calculation. The use of FE simulation was to validate and predict the wear data. The evolution of contact geometry and contact variables, including contact pressure and relative slip were studied. The implications of these predicted results are discussed with respect to fretting fatigue prediction, leading to new insight into the experimentally-observed effects of slip regime on crack initiation.